2023
DOI: 10.1186/s13054-023-04318-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinician perceptions of the impact of ICU family visiting restrictions during the COVID-19 pandemic: an international investigation

Abstract: Purpose To guarantee the safety of the public, clinicians and patients during the COVID-19 pandemic, hospital visits were severely restricted internationally. There are limited data on the precise impact of these visiting restrictions on Intensive Care Unit clinicians. Our objectives therefore were to explore the impact of family visitation restrictions on clinicians and care delivery and describe innovation alongside areas for potential improvement. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…McPeake et al. [24] also found some positive effects of family visiting restrictions on care provision more broadly. In addition, a study on orthopaedic patients reported that 24% of patients and 13% of relatives were satisfied with the non‐visit situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McPeake et al. [24] also found some positive effects of family visiting restrictions on care provision more broadly. In addition, a study on orthopaedic patients reported that 24% of patients and 13% of relatives were satisfied with the non‐visit situation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from the field of postpartum care, both the mothers and nurses described how visitor restrictions reduced distraction from visitors, promoting family bonding and allowing more time for higher-quality nursing care [23]. McPeake et al [24] also found some positive effects of family visiting restrictions on care provision more broadly. In addition, a study on orthopaedic patients reported that 24% of patients and 13% of relatives were satisfied with the non-visit situation.…”
Section: Discussionmentioning
confidence: 99%
“…In ICU, the impact of family visitation restrictions was well studied and associated in a qualitative study with clinician emotional exhaustion and emotional distress alongside the negative impact on job satisfaction. 33 Another study 34 revealed that among family members of patients hospitalised in the ICU with acute respiratory distress syndrome, COVID-19, compared with other causes of acute respiratory distress syndrome, was significantly associated with increased risk of symptoms of post-traumatic stress disorder at 90 days after ICU discharge. All these points suggest that the restriction of family visitation during the COVID-19 pandemic might be associated with worse prognosis of the relative, and need to be evaluated in operating room setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on similar studies that were previously described (18,19,21), our results seem robust. The COVID-19 pandemic has affected HCPs as well (26)(27)(28)(29) and may have influenced intervention delivery, warranting further research.…”
Section: Clinical Investigationsmentioning
confidence: 99%